COMMUNICATIVE SOCIAL INTERACTIONS AS AN EFFORT TO PREVENT RADICAL ISLAM IN STUDENTS - Umami, Ida (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2020)
This paper discusses the prevention efforts of radical understanding among students through communicative social interactions. This study is a literature study with a psychological approach. Data Research Methods use Library research derived from the literature, research results and various scientific articles and books collected with documentation techniques. The collected data is then analyzed using the content analysis method. This method is operationalized by making inferences – the inferences that can be imitated and valid for data by observing the context. The results of this research are social interactions are indispensable in student life as individuals and community members so communicate and assist and cooperate in achieving common goals desired. Positive social interactions will be able to be a sense of religious understanding among closed and textual students, so they feel as a group that feels most understanding of God's teachings. Therefore, there needs to be a better knowledge and understanding of religion for students and strive to conduct harmonious and communicative social interaction so that students can avoid and be prevented from understanding religious-based radicals and become a person who has a high social concern. Keywords: Communicative Social Interactions, Prevention, Radical Islam, Colleges